Clinical characteristics of maxillofacial fracture patients in Dr. M. Djamil General Hospital Padang - Hafiz, Al; Maidatuz Zahra, Agnesia; Mulyani, Henny; Huriyati, Effy; Revilla, Gusti; Zhuhra, Rahma Tsania (PERHATI-KL, 2024)
Background: Maxillofacial fracture consists of several types of fractures depending on their location. Traffic accidents are the most common cause of these cases. The choice of management given in maxillofacial fractures is divided into immediate and planned delayed management, depending on the condition of the injured tissue. Purpose: To describe the clinical characteristics of maxillofacial fracture in the Department of Otorhinolaryngology Faculty of Medicine Universitas Andalas/Dr. M. Djamil General Hospital Padang, in 2020 to 2022. Method: A descriptive study with retrospective approach. The study was conducted by collecting data from the medical record section by using a total sampling technique (59 patients) from 2020 to 2022. Result: The highest cause was traffic accidents (49.2%), the most common findings were nasal bone fracture (44.1%), with operative management (82.4%). Conclusion: Maxillofacial fractures were most commonly experienced by the young age group and caused by traffic accidents, therefore driving safety and driver compliance should be more emphasized. Keywords: maxillofacial fracture, ORIF (Open Reduction Internal Fixation), septorhinoplasty, septoplasty, rhinoplasty ABSTRAK Latar belakang: Fraktur maksilofasial terdiri dari beberapa jenis fraktur tergantung lokasinya. Kecelakaan lalu lintas menjadi penyebab tersering dari kasus ini. Pemilihan tatalaksana yang diberikan pada fraktur maksilofasial dibagi menjadi tatalaksana segera dan tatalaksana lanjutan terencana, tergantung dari kondisi jaringan yang terluka. Tujuan: Untuk mengetahui karakteristik klinis pasien fraktur maksilofasial di Departemen THT-BKL FK Unand/RSUP Dr. M. Djamil Padang, dari 2020 sampai 2022. Metode: Penelitian ini bersifat deskriptif dengan pendekatan retrospektif. Penelitian dilakukan dengan pengambilan data di bagian rekam medik dengan teknik total sampling dan didapatkan sampel sebanyak 59 pasien pada tahun 2020 sampai 2022. Hasil: kelompok usia paling sering adalah 16-30 tahun (54.2%), dengan jenis kelamin terbanyak adalah laki-laki (76.3%), penyebab tersering adalah kecelakaan lalu lintas (4.2%), jenis fraktur tersering adalah fraktur tulang hidung (44.1%), dan tatalaksana paling sering adalah tatalaksana operatif (82.4%) Kesimpulan: Fraktur maksilofasial paling sering dialami oleh kelompok usia remaja dan disebabkan kecelakaan lalu lintas, oleh karena itu keselamatan dan kepatuhan berkendara perlu lebih diperhatikan dan ditingkatkan. Kata kunci: fraktur maksilofasial, ORIF (Open Reduction Internal Fixation), septorinoplasti, septoplasti, rinoplasti